PENGARUH SERTIFIKAT HALAL TERHADAP MINAT DAN KEPUTUSAN PEMBELIAN KOSMETIK WARDAH DI KECAMATAN BARUMUN - Pebriani Nasution; Syamsul Effendi; Eli Agustami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
The purpose of this study was to determine the effect of halal certificates (X) on interest and purchasing decisions (Y) with a population of 22,042 people. From this population, a sample of 100 people was taken from residents in Barumun District. This type of research is quantitative descriptive where the relationship between the variables to the object under study is more cause and effect, so that in this research there are independent and dependent variables. The independent variable in this study is Halal Certificate, while the dependent variable is Wardah Cosmetics Purchase Interest and Decision in Barumun District. the data collection technique used is by using a questionnaire given to each respondent. The data is processed using SPSS Version 26.0 For Windows. The data analysis technique used is simple linear regression, with the formula Y=a+Bx+e. To find out how much influence the halal certificate has on the interest and purchasing decisions of Wardah cosmetics in Barumun District, a comparison technique of tcount with ttable is used for tcount ttable, thus Ha is accepted because tcount ttable. From the results of the validity test and questionnaire reliability test, each statement item is declared valid and reliable if rcount is greater than rtable with Cronbach's Alpha value 0.60. And obtained the Regression equation Y = 14,185 + 1,560 X + e, meaning that every 1% increase in Halal Certificate will cause an increase in Interest and Purchase Decision by 1,560%. While the value of the determinant coefficient (r2) was obtained at 0.805 or 80.5%, therefore it can be concluded that interest and purchasing decisions or independent variables have a significant effect on Wardah Cosmetics Halal Certificate or Bound Variables in Barumun District by 80.5%